From productivity to exporting or vice versa? Evidence from the Tunisian manufacturing sector - Mohamed Ayadi; Wided Mattoussi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper, we explore the link between firm productivity and exporting using three firm level datasets of 1323 Tunisian manufacturing firms from 2004 to 2006. In particular, we examine whether more productive firms self-select into export markets, and whether exporters achieve productivity improvements through learning by exporting effects. We then explore the link between innovation (as a channel linking productivity to exporting) and exporting. The analysis has been conducted on two clusters of firms. The first cluster distinguishes exporters from non-exporters and the second distinguishes fully exporting firms from others. The results suggest that fully exporting firms self-select more often into export markets and, therefore, have much less to gain from exporting because of their likely longer prior exporting experience. The analysis has been extended to deal with sectoral studies. The study finds that, in the long run, fully exporting firms in sectors characterized by subcontracting regimes, such as the textile and electronics industries, experience a distinct decline in the scope for learning by exporting. Moreover, the scope for learning might also be influenced by export destination, as in the case of the agro-food industries.
Keywords: F14; L63; L67; O55; 330; manufacturing industry; learning by exporting; self-selection; innovation; Tunisia